Responsiveness pelayanan keperawatan dengan kepuasan pasien di ruang rawat inap - Nafiz Naufal Hadhad; Yuni Kurniasih; Noor Ariyani Rokhmah (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Patient satisfaction is influenced by the quality of nursing services, one of which is responsiveness. Based on the results of a community satisfaction survey conducted by the Bantul Regency Health Office in 2025, patient satisfaction was recorded at 88.92%. This result indicates that patient satisfaction is below the minimum service standard set by the Indonesian Ministry of Health Regulation (PERMENKES) in 2016, which is >95%. Purpose: To determine the relationship between responsiveness of nursing services and patient satisfaction in inpatient wards. Method: This quantitative study used a descriptive cross-sectional design. The sampling technique used purposive sampling with a sample size of 100 respondents. The research instrument used a questionnaire. Data analysis used the Spearman Rank Test. Results: 62 respondents (62%) rated the responsiveness of nursing services as good, with the majority of patients being satisfied (89 respondents (89%). The Spearman Rank Test obtained a correlation coefficient of 0.416 with a p-value of 0.000 (p < 0.05). This indicates a significant relationship between responsiveness of nursing services and patient satisfaction in inpatient wards, with a positive relationship and moderate correlation strength. Conclusion: There is a relationship between responsiveness of nursing services and patient satisfaction in inpatient wards. Keywords: Nursing Service; Patient Satisfaction; Responsiveness. Pendahuluan: Kepuasan pasien dipengaruhi oleh mutu pelayanan keperawatan, salah satunya daya tanggap perawatan. Berdasarkan laporan hasil survei kepuasan masyarakat dinas kesehatan Kabupaten Bantul tahun 2025 tercatat kepuasan pelayanan 88.92%. Hasil tersebut menunjukkan kepuasan pasien berada dibawah nilai standar pelayanan minimal yang ditetapkan PERMENKES RI tahun 2016 yaitu >95%. Tujuan: Untuk mengetahui hubungan daya tanggap pelayanan keperawatan dengan kepuasan pasien di ruang rawat inap. Metode: Penelitian kuantitatif dengan rancangan deskriptif cross sectional. Teknik pengambilan sampel menggunakan Purposive Sampling dengan jumlah sampel 100 responden. Instrumen penelitian menggunakan kuesioner. Analisis data menggunakan Uji spearman rank Hasil: Daya tanggap pelayanan keperawatan kategori baik sebanyak 62 responden (62%) dengan kepuasan pasien sebagian besar berada pada kategori puas sebanyak 89 responden (89%). Hasil uji Spearman Rank diperoleh nilai koefisien korelasi sebesar 0.416 dengan p-value = 0.000 (p < 0.05). Hal ini menunjukkan terdapat hubungan yang signifikan antara daya tanggap pelayanan keperawatan dengan kepuasan pasien di ruang rawat inap dengan arah hubungan positif dan kekuatan korelasi sedang. Simpulan: Terdapat hubungan antara daya tanggap pelayanan keperawatan dengan kepuasan pasien di ruang rawat inap. Kata Kunci: Daya Tanggap; Pelayanan Keperawatan; Kepuasan Pasien.